New Technologies in Russian Cartographic Libraries - Kildushevskaya, Ludmilla; Kotelnikova, Natalya E. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
Only two years separate us from the third millennium. The most important feature of our time is the pervasive spread of information in society, with new technologies being promptly introduced in all fields of activity. This phenomenon could not pass by national libraries. It should be noted, however, that libraries are probably the most conservative institutions, and the older and richer a library is, the more difficult are the problems of its modernization. This observation has certain peculiarities with regard to cartographic libraries.